ATTEMPTS FOR BUILDING SUSTAINABLE LIVELIHOODS IN RURAL AREAS. SLOW FOOD PRESIDIA EXAMPLE (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2019)
The aim of this article is to show how and to what extent global ideas the Slow Food movement for sustainability and preservation of food biodiversity are implemented on a local level. The study examines different models and strategies of livelihoods in rural areas such as traditional ways of food production and alternative tourism focusing on the family role in the process of establishment, implementation and maintenance. The perceptions of locals towards the ideas of Slow Food and local products are presented. Crucial for building sustainable livelihoods are personal resources, entrepreneurial vision and government regulations to traditional homemamade foods.
Keywords: sustainability; rural areas; livelihoods; Slow Food movement; family enterprises